New Forensic Insight into Carl Auer von Welsbach's 1910 Observation of Induced Radioactivity: Theoretical, Experimental and Historical Approaches. (1st October 2016) - Steinhauser, Georg; Adunka, Roland; Hainz, Dieter; Löffler, Gerd; Musilek, Andreas
Abstract : In 1910, Carl Auer von Welsbach noted that he had made an observation of a radioactive substance inducing radioactivity to an inactive substance. From today's point of view, this could have been the first observation of neutron activation. Herein, we present new insights into our investigation of this 'mysterious observation' as Auer von Welsbach termed it. We believe that one of the activated objects was a platinum–iridium crucible. The dominating activation product of the crucible could have been iridium-194. We have discovered several platinum crucibles from Auer's heritage and investigated them by gamma-spectrometry and, one of them, by SEM/EDX. In the EDX investigations, however, no iridium was found in the most promising crucible. Hence this particular crucible was probably not the activated object. In any case, gamma-ray spectrometry revealed very low but detectable amounts of natural radionuclides. This indicated that these crucibles were used by Auer von Welsbach for his radioactive work and that these crucibles were bought prior to World War I. Hence Auer von Welsbach somehow managed to save these crucibles from the noble metal collections during the war. Auer's 1910 publication carried the suffix 'Part I', however, Part II was thought to be lost. In our recent work, however, we rediscovered a hand-written manuscript of Part II, in which the peculiar observation is mentioned vaguely. Lastly, we converted Auer's uranium standard into becquerels. Based on this conversion, we estimated that Auer von Welsbach observed an 194 Ir activity of the crucible of 500 kBq. It is further estimated that a (thermal) neutron flux density of approximately 8E+4 cm −2 s −1 was needed to activate the crucible in a way to meet Auer's description.